Leptin in Thrombosis and Atherosclerosis - Wang, Hui; Luo, Wei; Eitzman, Daniel T. (Current Pharmaceutical Design, 2014)
A world-wide obesity epidemic is threatening to have a major impact on the prevalence of chronic and acute vascular diseases. In addition to weight loss interventions, which have met with modest success to date, it will be important to understand mechanisms by which obesity promotes vascular disease processes. Studies of leptin, a hormone produced by the adipocyte, have supported the concept that adipocyte-specific products may be mediating some of the vascular risk associated with obesity. This mini-review provides an overview of some of the preclinical studies demonstrating causal relationships between leptin and vascular endpoints. Therapeutic strategies designed to block leptin-mediated signaling events in cells contributing to vascular disease may prove beneficial in obese subjects at risk for vascular complications.
Keywords: atherothrombosis